Mediterranean spotted fever and hearing impairment: a rare complication. (June 2015) - Rossio, Raffaella; Conalbi, Valeria; Castagna, Valentina; Recalcati, Sebastiano; Torri, Adriana; Coen, Massimo; Cassulini, Lucia Restano; Peyvandi, Flora
Highlights: Mediterranean spotted fever is characterized by the triad: fever, rash and eschar ( tache noire) The disease has a benign course, but severe forms can have cardiac, neurologic or renal involvement Hearing loss is an unusual complication of the disease Summary: Mediterranean spotted fever (MSF) is caused by Rickettsia conorii and transmitted by the brown dog tick Rhipicephalus sanguineus. It is prevalent in southern Europe, Africa and central Asia. The disease usually has a benign course and is characterized by fever, myalgia and a characteristic papular rash with an inoculation eschar ('tache noir') at the site of the tick bite. Severe forms of disease can have cardiac, neurologic or renal involvement. Nervous system complications are unusual and may develop in the early phase of disease or as a delayed complication. Neurological symptoms include headache and alterations of the level of consciousness, and some cases of meningoenchefalitis and Guillain-Barrè syndrome have been also reported. Peripheral nerve involvement is reported only in a limited number of case reports. We describe a case of Rickettsia conorii that was complicated with hearing loss and did not respond to specific treatment. Hearing loss is a rare event, but clinicians should be aware of this complication.